Welfare improving discrimination based on cognitive limitations - Oktay Sürücü (Bielefeld University, Center for Mathematical Economics (IMW), 2013)
This paper is concerned with the situation in which a profit-maximizing monopolist faces consumers that are diverse not only in their preferences but also in their levels of bounded rationality. The behavioral phenomenon considered here is the attraction effects when choices are made across categories. Using the standard second-degree price discrimination model, the optimal menu of contracts that screens consumers' types is characterized. The benefit of discriminating consumers based on their preference and cognitive limitation is always higher than its cost. In other words, the monopolist can exploit consumers and increase his profit with this contract. The model provides a possible explanation for the apparent puzzle why one may observe that the same quality products are priced differently under different labels. Moreover, this contract is welfare improving.
urn:nbn:de:0070-pub-26753085
Keywords: D03; D42; D60; D82; D86; 330; bounded rationality; attraction effect; contract design; welfare